Analysis of Cyanide Contents in Cassava Leaves (Manihot esculenta Crantz) Based on Boiling Time with Formation of Hydrindantin Complex by Using UV-Vis Spectrophotometry - Kadek N. Anjani; Baharuddin Hamzah; Paulus H. Abram (Jurnal Akademika Kimia, 2021)
This study aimed to determine cyanide contents in cassava leaves (Manihot esculenta Crantz) based on boiling time with the formation of hydrindantin complex using UV-Vis spectrophotometry. The variation of boiling time was 0, 5, 10, and 15 minutes respectively. The cyanide content was prepared by extracting the sample using water for 2 hours. Then the sample was distilled to obtain a distillate that containing cyanide. Determination of cyanide was carried out by reacting samples containing cyanide with 1% ninhydrin and 0.5% Na2CO3, then adding 1 M NaOH to form blue hydrindantin compounds in an alkaline condition. Blue hydrindantin compounds formed were analyzed by spectrophotometry at a maximum wavelength of 590 nm. The results showed that cyanide contents in cassava leaves based on boiling time 0, 5, 10, and 15 minutes respectively were 20.73 ppm, 13.92 ppm, 9.18 ppm, and 3.38 ppm. The longer the cassava leaves were boiled, the better it was to be consumed because it will significantly reduce cyanide contents.